Perancangan Web E-Commerce Brand Solipsism - VARDHA, REGITTA APRILLIE; HARIS, DARIUS ANDANA (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
The Solipsism brand focuses on exclusive clothing designs with limited production. Solipsism faces challenges in reaching consumers in a market dominated by fast fashion brands. This e-commerce web aims to expand market reach, increase sales, and strengthen brand identity. An attractive and user-friendly web design is expected to create a personalized and comfortable shopping experience for consumers. The web development uses the SDLC Waterfall model, which includes the stages of requirements analysis, design, implementation, testing, and maintenance. The main features provided include a product collection display and ordering system for users, as well as an admin page for product and order management. The results of blackbox testing show that all features function as needed with a 100% success rate in 34 test cases. Meanwhile, the System Usability Scale (SUS) results show that the user satisfaction level reaches 82.5% of the system functionality. This website is expected to help Solipsism compete better in the market and strengthen relationships with customers through an exclusive and attractive shopping experience.Keywords: E-commerce; Website; Waterfall; Fashion; Blackbox TestingÂ AbstrakBrand Solipsism berfokus pada desain baju eksklusif dengan produksi terbatas. Solipsism menghadapi tantangan dalam menjangkau konsumen di pasar yang didominasi oleh merek fast fashion. Web e-commerce ini bertujuan untuk memperluas jangkauan pasar, meningkatkan penjualan, dan memperkuat identitas brand. Desain web yang menarik dan ramah pengguna diharapkan menciptakan pengalaman berbelanja yang personal dan nyaman bagi konsumen. Pengembangan web menggunakan model SDLC Waterfall, yang meliputi tahap analisis kebutuhan, perancangan, implementasi, pengujian, dan pemeliharaan. Fitur utama yang disediakan antara lain tampilan koleksi produk dan sistem pemesanan untuk user, serta halaman admin untuk pengelolaan produk dan pesanan. Hasil pengujian blackbox testing menunjukkan bahwa seluruh fitur berfungsi sesuai kebutuhan dengan tingkat keberhasilan 100% pada 34 kasus pengujian. Sementara itu, hasil System Usability Scale (SUS) menunjukkan tingkat kepuasan pengguna mencapai 82,5% terhadap fungsionalitas sistem. Website ini diharapkan dapat membantu Solipsism bersaing lebih baik di pasar dan memperkuat hubungan dengan pelanggan melalui pengalaman belanja yang eksklusif dan menarik.Â